2007
DOI: 10.2165/00019053-200725100-00005
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Pegaptanib for the Treatment of Age-Related Macular Degeneration in the UK

Abstract: The results suggest that pegaptanib treatment is likely to be cost effective across all groups studied, and marginally more cost effective in younger patients and those with better pre-treatment VA. Cost effectiveness appears to be optimised if treatment is discontinued after 1 year if individual patients' VA has dropped by > or =6 lines from pre-treatment levels, or at any time if it drops below 6/95. However, strict application of discontinuation rules does not appear to be necessary for pegaptanib to be cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…d30 000 or $US50 000 per QALY gained); [2,24,27,37] a fifth study in the US showed that ranibizumab was dominant over usual care when caregiver costs were taken into account, but not cost effective when caregiver costs were excluded. [26] Of five pegaptanib studies, one UK analysis found pegaptanib to be clearly cost effective versus best supportive care over a 10-year time horizon; [23] the other four studies (including a UK HTA) showed that the cost effectiveness of pegaptanib varied considerably depending on the stage of disease and time horizon. [2,11,21,22] Nine studies provided cost-utility analyses of PDT with verteporfin compared with no treatment, usual care or best supportive care, reflecting that this is an older treatment option for wet AMD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…d30 000 or $US50 000 per QALY gained); [2,24,27,37] a fifth study in the US showed that ranibizumab was dominant over usual care when caregiver costs were taken into account, but not cost effective when caregiver costs were excluded. [26] Of five pegaptanib studies, one UK analysis found pegaptanib to be clearly cost effective versus best supportive care over a 10-year time horizon; [23] the other four studies (including a UK HTA) showed that the cost effectiveness of pegaptanib varied considerably depending on the stage of disease and time horizon. [2,11,21,22] Nine studies provided cost-utility analyses of PDT with verteporfin compared with no treatment, usual care or best supportive care, reflecting that this is an older treatment option for wet AMD.…”
Section: Discussionmentioning
confidence: 99%
“…A UK-based analysis by Wolowacz et al [23] showed treatment with pegaptanib to be cost effective relative to best supportive care for subfoveal wet AMD over a 10-year timeframe from a governmental perspective; ICERs were lower when visual acuity at treatment initiation was better. However, an HTA by Colquitt et al [2] calculated higher costs per QALY gained over the same timeframe and from a similar perspective.…”
Section: Cost Utilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Efficacy and safety analyses were recently reported in two randomized, sham-controlled, clinical trials. [25,26] The two combined trials, known as the VISION (VEGF Inhibition Study in Ocular Neovascularisation) study, enrolled 1186 patients. Patients received either an intraocular injection of pegaptanib or a similar sham injection every 6 weeks.…”
Section: Aptamer Therapymentioning
confidence: 99%
“…Visual acuity (VA) was measured using Snellen eye charts, during which patients were asked to identify specific sized letters or lines at a set distance. [25,26] The VISION study demonstrated a significant difference in loss of VA by 1 year in patients who received pegaptanib as compared with those who received sham injection (a loss of 7.93 letters for pegaptanib vs 15.05 letters for sham; p < 0.0001), which was maintained at 2 years. [25,26] The risk of severe loss of VA (loss of 30 letters or more) from baseline was 22% in the sham-injection group and 10% in the pegaptanib group (p < 0.001).…”
Section: Aptamer Therapymentioning
confidence: 99%